ANTI-CHOLESTEROL ACTIVITY TEST OF N-HEXANE, METHANOL AND ETHANOL EXTRACTS ETHANOL EXTRACT OF LEMON PEEL WITH UV-VIS SPECTROPHOOMETRY METHOD - Mila Mila; Titin Supriatin; N. Ai Erlinawati (STIKes Karsa Husada Garut, 2023)
Cholestrol is a fatty substance that is in and produced by the liver and is needed by the body.However, if cholesterol in the blood is too high it can cause blockages in blood vessels that can trigger various other types of more serious diseases such as heart disease, stroke and high blood pressure (inflammation of the pancreas organ), diabetes mellitus, thyrod disorders, etc. Lemon peel can reduce cholesterol levels in the body. Because lemon peel contains flavonoid polyphenols, which are very active in lowering cholesterol. The purpose of this study was to determine the anti-cholesterol activity and determine the EC50 value of N-Hexane partition, methanol and ethanol extracts of lemon peel (Citrus limon) invitro. This type of research is descriptive quantitative analysis method using UV-Vis spectrophotometry at a wavelength of 665.0 nm with a concentration series of test samples 150 ppm, 300 ppm, 450 ppm, 600 ppm, 750 ppm. The research data showed that the level of cholesterol reduction was directly proportional to the increase in concentration in the sample. The EC50 value of n-hexane partition was 7.6 ppm, methanol partition was 108.53 ppm and ethanol extract was 194.9231 ppm. Conclusion among the three partitions, n-hexane extract is the most effective to reduce cholesterol.